Evolution of cost recovery levels in the Portuguese water supply and wastewater industry 1998-2005 - Monteiro, Henrique (2012)
This paper assesses the situation in Portugal in 2005 regarding cost recovery in the water supply (WS) and wastewaterdrainage and treatment (WWDT) industry by type of system (bulk and retail water and wastewater), by type of utility and by NUTS III, halfway between the publication of the Water Framework Directive (WFD) and the meeting of the 2010 deadline. For that purpose, we build on the previous contribution by Monteiro (2007), which reported the situation in 2002, by updating the indicators to 2005 and assessing the evolution since 1998. We also present a brief historical overview of the presence of the cost recovery principle in Portuguese law regarding the industry. The main conclusions that stand out are: the introduction of the cost recovery principle is prior to the WFD and the more recent Water Law, although it lacked practical implementation; the level of revenues collected by the WS and WWDT utilities is insufficient to meet the financial costs of their activities; the situation is worse for wastewater than for WS systems, revealing evidence of cross-subsidization within the utilities which manage both systems; the situation has worsened in recent years; cost recovery levels are lower in the less densely populated and poorer inland regions; finally, we find no evidence associating cost recovery levels and the type of utility.